Nitrogen utilization and nutrient intake and digestibility can be improved in sheep fed cotton-burrs with crude glycerin - Paiva, P. G.; Rebelo, L. R.; Gomes, R. S.; Zanchetin, M.; Baroni, A. P.G.; Godoy, H. P.; Pereira-Junior, S. A.G. [UNESP]; Del Valle, T. A.; Abreu, J. G.; Zervoudakis, J. T.; Cabral, L. S.; Galati, R. L. (Elsevier, 2022)
The present study evaluated the replacement of corn grain with increasing levels of crude glycerin (CG) in cotton burrs-based diets for sheep in terms of intake and digestibility, nitrogen (N) metabolism, microbial protein synthesis (MPS) efficiency, blood glucose, and ruminal parameters. Five male sheep (body weight 52.2 ± 5.5 kg), castrated and rumen-fistulated, were used in a randomized 5 × 5 Latin square design. The experimental period consisted of 17 d (10 d for adaptation and 7 d for sampling). Isonitrogenous diets with 112 g crude protein (CP) per kg dry matter (DM) were formulated to contain 0 (control), 50, 100, 150, and 200 g CG/kg DM. Compared to the control diet, feeding CG up to 200 g/kg DM quadratically changed (P < 0.01) nutrient intake. Maximum intake of DM, organic matter (OM), neutral detergent fiber (aNDF), and water was achieved when feeding 150 g CG/kg DM. Compared to zero CG inclusion, feeding 200 g CG/kg DM linearly increased (P ≤ 0.03) the digestibility of OM and aNDF by 3.4 % and 13.6 %, respectively, while DM digestibility tended to increase linearly by 6 % (P = 0.05). The apparent N digestibility increased linearly (P < 0.02) by 6.8 % and 10.4 % with GC inclusion levels of 150 and 200 g/kg DM, respectively. Nitrogen intake, fecal and urinary N, absorbed N, and N absorbed per unit of N intake were all quadratically changed (P ≤ 0.03) by CG inclusion. These parameters increased by 34.7 %, 15.7 %, 34.5 %, 49.3 %, and 10.7 %, respectively, when a diet of 150 g CG/kg DM was fed. Feeding different levels of CG in a sheep diet did not affect (P ≥ 0.12) ruminal MPS (g microbial N/d) and MPS efficiency (g microbial CP/kg total digestible nutrients), ruminal pH, and concentrations of ruminal ammoniacal-N and blood glucose. Crude glycerin included up to 150 g/kg in cotton burrs-based diets for sheep improved N utilization and intake and digestibility of nutrients without affecting ruminal parameters, glucose blood concentrations, and MPS efficiency.
Keywords: Byproducts; Corn; Cotton burrs; Energy; Glucose; Glycerol